Unique organization of the human BCR gene promoter. - Zhu, Q S (1990)
The promoter of the human BCR gene, regulating the transcription of the chimeric BCR/ABL mRNA in leukemia, has been isolated and characterized. A region of 1.1 kb immediately 5' to the transcription start site was analyzed in detail by sequencing, DNase 1 footprinting, gel retardation and functional studies. These experiments localized a minimal promoter to a 650 bp sequence, composed of 270 bp of 5' flanking sequences and 380 bp of exon 1 transcribed sequences. The promoter region includes a TTTAA box, one Sp1 site and a novel protein-binding sequence absolutely necessary for efficient transcription in vivo. Six additional protein-binding regions were identified more to the 5'. Of these, one is found in an inverted repeat in the 3' coding and splice donor region of BCR exon 1.